2019
DOI: 10.1002/jcp.28216
|View full text |Cite|
|
Sign up to set email alerts
|

Galangin ameliorates cardiac remodeling via the MEK1/2–ERK1/2 and PI3K–AKT pathways

Abstract: Cardiac remodeling is associated with inflammation and apoptosis. Galangin, as a natural flavonol, has the potent function of regulating inflammation and apoptosis, which are factors related to cardiac remodeling. Beginning 3 days after aortic banding (AB) or Sham surgery, mice were treated with galangin for 4 weeks. Cardiac remodeling was assessed according to echocardiographic parameters, histological analyses, and hypertrophy and fibrosis markers. Our results showed that galangin administration attenuated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 32 publications
(63 reference statements)
1
28
0
Order By: Relevance
“…Liao et al reported that myocardin expression is induced in cardiac hypertrophy, and its overexpression in neonatal rat cardiomyocytes induces hypertrophy (Liao et al, 2011). GA significantly ameliorated cardiac function and inhibited cardiac hypertrophy and fibrosis by disruption of PI3K-Akt-GSK3β and MEK1/ 2-ERK1/2-GATA4 signaling and via Ang II stimulation (Wang et al, 2013;Wang et al, 2019). According to the present findings, GA plays an important protective role in regulating cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 74%
“…Liao et al reported that myocardin expression is induced in cardiac hypertrophy, and its overexpression in neonatal rat cardiomyocytes induces hypertrophy (Liao et al, 2011). GA significantly ameliorated cardiac function and inhibited cardiac hypertrophy and fibrosis by disruption of PI3K-Akt-GSK3β and MEK1/ 2-ERK1/2-GATA4 signaling and via Ang II stimulation (Wang et al, 2013;Wang et al, 2019). According to the present findings, GA plays an important protective role in regulating cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 74%
“…Recently, Wang et al [86] have suggested that galangin may also protect against cardiac remodeling by decreasing inflammatory responses and apoptosis. Its action was associated with the inhibition of PI3K-Akt-GSK3β signaling pathways.…”
Section: Honey Phenolics and Cardiovascular Diseasesmentioning
confidence: 99%
“…MAPKs, including JNK, P38 and ERK1/2, are leading factors in GA attacks. Mitogen-activated protein kinase kinase4/7 (MKK4/7), mitogen-activated extracellular signal-regulated kinase1/2 (MEK1/2) and MKK3/6 are upstream kinases of JNK, ERK1/2 and P38, respectively [25][26][27]. In this study, RDN reduced the abnormal expression of MKK4, pMEK1/2, p-JNK and p-ERK1/2.…”
Section: Discussionmentioning
confidence: 68%